Means of Question-Answer Interaction for Collaborative Development Activity - Petr Sosnin (Advances in Human-Computer Interaction)
The key problem of successful developing of the software intensive system (SIS) is adequate conceptual interactions of stakeholders at the early stages of designing. Nowadays the success of development is extremely low. It can be increased with using artificial intelligence (AI) means including models of reasoning supported by the human-computer interaction in collaborative development activity. In this paper, a number of question-answer means for modeling reasoning are suggested. Such kind of means is defined and implemented in order to get effects of integrating the collective reasoning for their positive influence on the intellectual activity of designers. Question-answer means are arranged as a specialized processor opening the possibility to question-answer programming of the tasks on the conceptual stage of designing. Suggested and investigated means can be used for solving any complicated task.